TWO ATTRIBUTIVE POSSESSIVE CONSTRUCTIONS IN PAGU: THE DOUBLE AND SINGLE MARKING - Perangin Angin, Dalan Mehuli (Linguistik Indonesia, 2024)
This paper discusses two different attributive possessive constructions in Pagu, a West Papuan language spoken in Halmahera. They can be categorized into double and single marking. Semantically, the former construction allows only human possessor, while the latter both non-human and human – with a restricted use for human on the core kinship relations only. The paper also discusses the definiteness of the possessor or possessee in each construction, which I argue result from the familiarity of both the possessor-possessee after being introduced in the discourse. It also allows either the possessor or the possessee to occur alone. The structure of each of the constructions will be presented in the Role and Reference Grammar’s Layered Structure of the Noun Phrase. It will help us see the functions of each possessive marker and the relation between the possessor and possessee.